Histo-Pathological Evaluation of Breast Cancer after Neo-Adjuvant Chemotherapy - Muhammad Sami Ullah, Shaiza Nasir, Saddaf Hina, Kinza Tahir, Muhammad Zafar Rana, Atifa Rashid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A recent standardized therapeutic technique for the patients having advanced and large (bigger than two centimeters) breast cancer is neo-adjuvant chemotherapy. The gold standard is the histo-pathological assessment of carcinoma response. Methodology: In this research study, we performed the histo-pathologic evaluation of forty-four samples received in the pathology department over a period of one year from 1 July 2021 to 30 June 2022. Results: In this research study, we studied total forty-four patients with breast cancer. Average age of these females was fifty years. Average size prior CT was 56.140 centimeter square and post CT was 29.4 centimeter square. In this research work, complete pathologic response was shown by eighteen percent patients and incomplete response was shown by eighty-four percent patients. Conclusion: Changes in pattern of characterizations examined after the histo-pathological evaluation of tumor are dystrophic calcification, stromal hyalinization, regions of coagulated necrosis, reactive infiltration of lymphocytes, cellular fibrous tissue and hemosiderin laden macrophages. Keywords: Characterization, pathology, evaluation, neo-adjuvant chemotherapy, carcinoma, cancer, average.